Painting the Rocks: The Loss of Old Sydney. THE MUSEUM OF SYDNEY, SYDNEY, AUSTRALIA - Tector, Amy (Archivaria, 2011)
Painting the Rocks: The Loss of Old Sydney. THE MUSEUM OF SYDNEY, SYDNEY, AUSTRALIA. Mounted at The Museum of Sydney, 7 August–28 November 2010.